Faktor Sosial Ekonomi dan Budaya yang Mempengaruhi Usahatani Kelapa di Kabupaten Kepulauan Talaud - DANIEL J. TORAR (Buletin Palma, 2009)
Social Economic and Culture Factors that Influence Coconut Farm in Talaud Island RegencyThis research was done in order to study social economic and culture factors that influence farmer income at coconut farm in Talaud Island Regency. This research was conducted by survey method with descriptif analytis approach in Kabaruan and Beo Sub District, Talaud Island from August to October 2005. A total of four villages were chosen randomly, two villages in each Sub District. In each village, 30 farmers were chosen randomly as respondents, maturing total 120 farmers. The result of multiple regression analysis showed that factors influenced at the coconut farm in Talaud Island Regency were culture value variable, extension approach variable, distance of farmer house to coconut farm variable, characteristic of technologi variable, and farmer motivation variable. Dominant factor which determines coconut farmer’s rate of return is the farmer motivation.